I can't prove (n - 0) = n with Idris
I am trying to prove, what to my mind is a reasonable theorem: theorem1 : (n : Nat) -> (m : Nat) -> (n + (m - n)) = m Proof by induction gets to the point where me need to prove this: lemma1 : (n : Nat) -> (n - 0) = n This is what happens when I try to prove it (the lemma, for simplicity sake) using the interactive prover: ---------- Goal: ---------- {hole0} : (n : Nat) -> minus n 0 = n > intros ---------- Other goals: ---------- {hole0} ---------- Assumptions: ---------- n : Nat ---------- Goal: ---------- {hole1} : minus n 0 = n > trivial Can't unify n = n with minus n 0 = n Specifically: